2005
DOI: 10.3200/socp.145.2.225-236
|View full text |Cite
|
Sign up to set email alerts
|

Audience Perceptions of Candidates' Appropriateness as a Function of Nonverbal Behaviors Displayed During Televised Political Debates

Abstract: Compared to televised debates using a single-screen format, such debates using a split screen presenting both debaters simultaneously show viewers the nonverbal reactions of each debater's opponent. The authors examined how appropriate or inappropriate such nonverbal behaviors are perceived to be. Students watched one of four versions of a televised debate. One version used a single-screen format, showing only the speaker, whereas the other three versions used a split-screen format in which the speaker's oppod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Yet another study using the same design found that any antagonistic background behavior displayed by an opponent was perceived as inappropriate (Seiter & Weger, 2005), suggesting, perhaps, that the low credibility ratings reported in earlier studies might have occurred because antagonistic background behavior is perceived as rude. If that is the case, we wonder if such negative perceptions might be attenuated if the background behavior displayed by an opponent was not purely antagonistic.…”
Section: Review Of Literaturementioning
confidence: 93%
See 4 more Smart Citations
“…Yet another study using the same design found that any antagonistic background behavior displayed by an opponent was perceived as inappropriate (Seiter & Weger, 2005), suggesting, perhaps, that the low credibility ratings reported in earlier studies might have occurred because antagonistic background behavior is perceived as rude. If that is the case, we wonder if such negative perceptions might be attenuated if the background behavior displayed by an opponent was not purely antagonistic.…”
Section: Review Of Literaturementioning
confidence: 93%
“…For example, instead of showing only disagreement with a speaker, what if the debater in the background indicated some disagreement and some agreement during an opponent's speech? Although previous research has called for such an investigation (see Seiter & Weger, 2005), to date, there has not been one.…”
Section: Review Of Literaturementioning
confidence: 94%
See 3 more Smart Citations